2022
DOI: 10.1007/s00432-021-03908-9
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities in endometrial cancer survival in Germany: a survival analysis using population-based cancer registry data

Abstract: Purpose Area-based socioeconomic deprivation has been established as an important indicator of health and a potential predictor of survival. In this study, we aimed to measure the effect of socioeconomic inequality on endometrial cancer survival. Methods Population-based data on patients diagnosed with endometrial cancer between 2004 and 2014 were obtained from the German Centre for Cancer Registry Data. Socioeconomic inequality was defined by the German I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Factors such as differential access to health care, level of income, educational status and areal-level economic deprivation may be contributory. Bedir and colleagues analyzed data on 21,602 German women with endometrial cancer and found differences in survival according to district level socioeconomic deprivation (170). In a Swedish study, women from the higher social groups were less likely to be diagnosed with advanced stage disease and non-endometrioid cancers, and had more favourable outcomes than women from the lower social groups (171).…”
Section: Sociodemographic Associations With Prognosismentioning
confidence: 99%
“…Factors such as differential access to health care, level of income, educational status and areal-level economic deprivation may be contributory. Bedir and colleagues analyzed data on 21,602 German women with endometrial cancer and found differences in survival according to district level socioeconomic deprivation (170). In a Swedish study, women from the higher social groups were less likely to be diagnosed with advanced stage disease and non-endometrioid cancers, and had more favourable outcomes than women from the lower social groups (171).…”
Section: Sociodemographic Associations With Prognosismentioning
confidence: 99%
“…Survival analysis methods such as nonparametric Kaplan–Meier (KM) method and semi-parametric Cox proportional hazards (CPH) regression models have been proposed to study time to recurrence and death following the diagnosis of EC [ 2 – 6 ]. For the semi-parametric CPH method, different covariates have been included in the regression model, from social economic factors [ 7 ] to clinical and radiomic factors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%